(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Ensuring the safe utilization of electrical energy by the general populace is a critical aspect of public safety and infrastructure reliability. This article examines the imperative of establishing comprehensive safety requirements for electrical energy usage, focusing on common hazards, regulatory frameworks, and best practices to mitigate risks. By implementing robust safety measures and fostering public awareness, societies can significantly reduce incidents related to electrical hazards, thereby safeguarding lives and property.